Is dermatoglyphics an object of scientific research or not? - A. Kh. Ashirmetov; I. R. Mavlyanov; A. A. Sadikov (National Electronic Information Consortium (NEICON), 2020)
The versatility of human nature implies a great difficulty in its comprehending and determines many methods and approaches to its study. Dermatoglyphics is one of such methods, that studies the structure of the skin patterns of palmar and plantar surfaces of the hands and feet. This article reviews data related to finger dermatoglyphics informativity in various scientific disciplines. Dermatoglyphic patterns are formed under the influence of environmental factors and polygenic hereditary factors. Signs of papillary patterns are also determined by polygenic factors that are inherited from parents. Like any hereditary traits, they can mutate. Mutations and hereditary diseases accompanied by damaging of the genetic code, as a rule, manifest in the phenotype and in the characteristics of dermatoglyphs. Informativity and lability of dermatoglyphic pattern allows to use it as a factor - indicator of susceptibility to a particular disease with hereditary component. Currently, in sports genetics, dermatological markers of the fingers are also widely used to determine individual predisposition to a certain motor activity and sports talent. Study of combinations of types of patterns of dermatoglyphic characteristics of the toes, as well as the analysis of finger and plantar lines, types of dermatological patterns of the foot, allows using the foot dermatoglyphics as the additional marker of a genetic predisposition to a particular sport. As a constitutional marker the dermatoglyphics has prerequisites for predicting manifestations of a person's individuality in all its diversity of physical, physiological and mental properties. Attempts to identify the informativity of finger dermatoglyphics in the field of professional selection were made earlier by representatives of various sports.